DEFENSE AND REVITALIZATION OF MALAY LANGUAGE - Emawati Emawati; Emzir Emzir; Zainal Rafli (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The purpose of this research is to describe in depth about Palembang Malay language defense in Palembang. Data analysis was done by using the method of ethnography according to Spradley with progressive stretching sequence (developmental research sequence Spradley). Data collection techniques were conducted through interviews, observation, field notes, document studies, questionnaires, and photography. The steps taken by the researcher are (1) the determination of focus, (2) the submission of questions, (3) data collection, (4) analyzing and interpreting data. Further data analysis technique is done using Spradley (ethnography) model. Researchers analyzed field data collected from observations of participants to find questions. Furthermore, researchers analyzed field notes. There are four types of analysis: domain analysis, taxonomic analysis, component analysis and theme analysis. Based on the results of the analysis can be concluded that all domains still use Palembang Malay language in everyday life. Nevertheless on the research findings, researchers also found some vocabulary that has been rarely used in the conversation / daily communication of Palembang Malay society. Factors that threaten the existence of Palembang Malay language is the entry of immigrants from the outside, the natives of Palembang who moved to other areas, marriage antardaerah Palembang city. Efforts that can be made for the defense and revitalization of Palembang Malay language is to make Palembang Malay as a subject in school, menghidupuburkan Palembang Malay language use in the mass media and support from the local government for Palembang Malay language defense by creating a special law that discusses the use of language Malay Palembang so that it can continue to survive and develop so avoid the extinction.